SANITIZATION, A GROUNDED APPROACH OF VIRAL INFECTIONS AVOIDANCE FOR HUMAN HEALTH: COVID-19, A STIMULUS OF PUBLIC HEALTH POLICY MODERATION ON COMMUNICABLE DISEASES IN UGANDAN COMMUNITIES. A DESCRIPTIVE, CROSS-SECTIONAL AND CORRELATIONAL STUDY. - Kiggundu, Ssegawa E James (Student's Journal of Health Research Africa, 2023)
Background: This study established how sanitization for viral infection avoidance stimulates public health policy moderation on communicable diseases, specifically examining existing health policy on viral infection avoidance and shortfalls; establishing how sanitization stimulates policy moderation; how sanitization and policy moderation impact viral infection avoidance for human health in Ugandan communities. Methods: The study targeted a population of 1645 based on levels of vulnerability and managing prophylaxis function. A positivistic approach engaged a cross-sectional survey design. Data analysis took descriptive statistics, correlational, and regression analysis. Purposive, simple random sampling was used. Results: Existing policies influencing viral infection avoidance performed below 20%, inappropriate, promote creations of remedy extracts, soap solutions, detergents, boiled herbal mixtures steaming with acceptance and compliance revealed at 13.4%, negatively impacting viral infection avoidance by 4.5%, implementation by 46.5%. Policy exhibited low positive correlations with awareness and mindset change contributing 27.1% and 36.7% respectively, impacting sanitization by 13.7%. Sanitization significantly impacted policy by 29.7% twice as much. Eminent change in coefficients of determination from 0.352 models (1) to 0.113 models (2) and 0.025 models (3) suggested regressing the existing main policy to a generically decomposed accommodating inclusion modality supporting efficacy and efficiency. Conclusions: Awareness of viral infections was significantly low. Existing policies don’t suggest representative contingency methods, enforcement, implementations, and realistic techniques for viral infections and pathogens avoidance. Sanitization glossily moderates policy grounding it inclusive in enforcing avoidance of candidate viral infections by 29.7% and positively influences viral infections avoidance cumulatively by 48.4%, Recommendations: MoH should dedicate sensitization programs for people lacking knowledge of transmission of communicable diseases, provide alternative policies to healthcare livelihood and service delivery instead of locking down areas of high human concentrations, and issue guidelines and standards ensuring sustainable health security for self-provided gargets and remedies to avoid further infection and reinfection due misuse.